2016
DOI: 10.18632/oncotarget.8910
|View full text |Cite
|
Sign up to set email alerts
|

Folate deficient tumor microenvironment promotes epithelial-to-mesenchymal transition and cancer stem-like phenotypes

Abstract: Clinically, serum level of folate has been negatively correlated to the stage and progression of liver cancer. Nevertheless, the functional consequence of folate deficiency (FD) in malignancy has not been fully investigated. Human hepatocellular carcinoma (HCC) cells (as study model) and other cancer types such as lung and glioma were cultured under folate deficient (FD) and folate complete (FD) conditions. Molecular characterization including intracellular ROS/RNS (reactive oxygen/nitrogen species), viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
2
28
1
Order By: Relevance
“…In concordance with recent advances in CSC malignancy development as cancer stem cell diseases, 2 the present study provides several first lines of evidence to signify the LFMS-induced CSC-like potentials of human CRC tissues and cells: (1) induced transcript and protein expressions of the pluripotent-associated Shh signaling markers; (2) activated trans-differentiation by regulation of EMT markers; (3) induced expressions of the pluripotent CSC markers (SOX2, OCT4 and NANOG); (4) increased MMP2/MMP9 enzymatic digestion on matrix protein for invasion; (5) promoted CSC self-renewal capability of anchorage-independent tumor-spheroid formation. LFMSinduced CSC-like potentials of human CRC was consistent with few studies on the xenograft mouse model of liver cancers, 30 antifolate-treated non-small cell lung cancers 31 and colonic cancers. 32 In line with the robust activation of the Shh-Gli pathway required for expressing stemness potentials in different cancer contexts, 7-12 blockage of FD-activated Shh signaling by CYC abolished FD-promoted SOX2 gene expression, EMT trans-differentiation, oncosphere formation and subsequently abrogated FD-enhanced invasion of human adenocarcinoma cells.…”
Section: Discussionsupporting
confidence: 87%
“…In concordance with recent advances in CSC malignancy development as cancer stem cell diseases, 2 the present study provides several first lines of evidence to signify the LFMS-induced CSC-like potentials of human CRC tissues and cells: (1) induced transcript and protein expressions of the pluripotent-associated Shh signaling markers; (2) activated trans-differentiation by regulation of EMT markers; (3) induced expressions of the pluripotent CSC markers (SOX2, OCT4 and NANOG); (4) increased MMP2/MMP9 enzymatic digestion on matrix protein for invasion; (5) promoted CSC self-renewal capability of anchorage-independent tumor-spheroid formation. LFMSinduced CSC-like potentials of human CRC was consistent with few studies on the xenograft mouse model of liver cancers, 30 antifolate-treated non-small cell lung cancers 31 and colonic cancers. 32 In line with the robust activation of the Shh-Gli pathway required for expressing stemness potentials in different cancer contexts, 7-12 blockage of FD-activated Shh signaling by CYC abolished FD-promoted SOX2 gene expression, EMT trans-differentiation, oncosphere formation and subsequently abrogated FD-enhanced invasion of human adenocarcinoma cells.…”
Section: Discussionsupporting
confidence: 87%
“…Concomitantly, E-cadherin was found to be severely downregulated. 23 This phenomenon is ascribable to the promotion of epithelial-to-mesenchymal transition (EMT) evoked by FAD-induced ONS. Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…The human HL-7702 and QGY-7703 cell lines were selected because folate deficiency has been identified as an important risk factor for HCC, and alterations in the expression of miRNAs have been shown to be prominent events during the early stages of liver carcinogenesis [32]. Su YH et al [33] showed that a folate-deficient tumor microenvironment promoted epithelial-to-mesenchymal transition in hepatocytes. Chem CL et al[34]demonstrated that FA deficiency induced OS and apoptosis in the well-differentiated HCC cell line HepG2.…”
Section: Methodsmentioning
confidence: 99%